2013
DOI: 10.1051/0004-6361/201321185
|View full text |Cite
|
Sign up to set email alerts
|

Observationally driven 3D magnetohydrodynamics model of the solar corona above an active region

Abstract: Aims. The goal is to employ a 3D magnetohydrodynamics (MHD) model including spectral synthesis to model the corona in an observed solar active region. This will allow us to judge the merits of the coronal heating mechanism built into the 3D model. Methods. Photospheric observations of the magnetic field and horizontal velocities in an active region are used to drive our coronal simulation from the bottom. The currents induced by this heat the corona through Ohmic dissipation. Heat conduction redistributes the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(122 citation statements)
references
References 32 publications
14
108
0
Order By: Relevance
“…These models show that the energy is predominantly deposited in quantities of about 10 17 J , consistent with the predictions of nanoflares by Parker (1988). Recently, observed coronal structures could be reproduced by the 3D coronal models based on the observed magnetic field and flows in the photosphere alone (Bourdin et al 2013), and the constant cross section of loops was reproduced (Peter & Bingert 2012). While the above models are all based on DC-type Ohmic heating, recently van Ballegooijen et al (2011) studied the AC energy input by Alfvén wave turbulence in a coronal magnetic flux tube using a reduced magnetohydrodynamics (MHD) approach and found it sufficient to heat the hot coronal loops.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…These models show that the energy is predominantly deposited in quantities of about 10 17 J , consistent with the predictions of nanoflares by Parker (1988). Recently, observed coronal structures could be reproduced by the 3D coronal models based on the observed magnetic field and flows in the photosphere alone (Bourdin et al 2013), and the constant cross section of loops was reproduced (Peter & Bingert 2012). While the above models are all based on DC-type Ohmic heating, recently van Ballegooijen et al (2011) studied the AC energy input by Alfvén wave turbulence in a coronal magnetic flux tube using a reduced magnetohydrodynamics (MHD) approach and found it sufficient to heat the hot coronal loops.…”
Section: Introductionsupporting
confidence: 80%
“…2.3). Our previous models (e.g., Bingert & Peter 2011Bourdin et al 2013) used an observed magnetic field and an observed or generated velocity field to prescribe the bottom boundary conditions, which was then driving the model. Here we impose the properties from the flux-emergence simulation in a similar fashion.…”
Section: Coronal Modelmentioning
confidence: 99%
“…On the other hand, the field-line braiding mechanism proposed by Parker (1972) induces currents in the corona that are dissipated by Ohmic (direct current, DC) heating. This is described well in magneto-hydrodynamics (MHD), and observationally driven computational models show an energy input together with a dissipation mechanism that creates loop structures within the corona that compare well to observations (Bourdin et al 2013(Bourdin et al , 2015.…”
Section: Introductionsupporting
confidence: 61%
“…We selected field lines that (a) are closed and do not connect to the upper box boundary; (b) have a length of 18 Mm to 150 Mm; and (c) reach a minimum temperature of at least 75 000 K before reaching a height of 18 Mm. We also made sure that the field lines crossing the EUV-intensity maximum of the most prominent loops (SL 1-3 and CL 1+2; see Bourdin et al 2013) were included in this ensemble of about 67 000 field lines, as well as approximately 200 field lines neighboring these loops.…”
Section: Coronal Model and Field-line Ensemblementioning
confidence: 99%
“…In general, loop structures found in observations, such as thin or thick loops at constant cross section, or expanding envelopes of several thin loops, are also seen in the three-dimensional MHD models [103]. A three-dimensional MHD model that was run to match an actual observation did even reproduce the location of a set of loops in three-dimensional space, as revealed by a comparison to stereoscopic observations [48].…”
Section: (A) Synthetic Observationsmentioning
confidence: 82%